Unformatted text preview: w = c + di for real numbers a, b, c and d. Then
zw = (a + bi)(c + di). After the usual arithmetic9 we get zw = (ac − bd) + (ad + bc)i. Therefore,
zw =
=
= √
√ = a2 c2 − 2abcd + b2 d2 + a2 d2 + 2abcd + b2 c2 Expand √ a2 c2 + a2 d2 + b2 c2 + b2 d2 Rearrange terms a2 (c2 + d2 ) + b2 (c2 + d2 ) =
= (ac − bd)2 + (ad + bc)2 Factor (a2 + b2 ) (c2 + d2 )
√
a2 + b2 c2 + d2 Factor
Product Rule for Radicals = z w Deﬁnition of z  and w Hence zw = z w as required.
Now that the Product Rule has been established, we use it and the Principle of Mathematical
Induction10 to prove the power rule. Let P (n) be the statement z n  = z n . Then P (1) is true
since z 1 = z  = z 1 . Next, assume P (k ) is true. That is, assume z k = z k for some k ≥ 1.
Our job is to show that P (k + 1) is true, namely z k+1 = z k+1 . As is customary with induction
proofs, we ﬁrst try to reduce the problem in such a way as to use the Induction Hypothesis.
= zk z = z k+1 zk Properties of Exponents
z  Product Rule z k z  = = z k+1 Indu...
View
Full Document
 Fall '13
 Wong
 Algebra, Trigonometry, Cartesian Coordinate System, The Land, The Waves, René Descartes, Euclidean geometry

Click to edit the document details